2005
DOI: 10.1111/j.1468-3083.2005.01204.x
|View full text |Cite
|
Sign up to set email alerts
|

Screening of Chlamydia trachomatis urogenital infections among the male and female population of the Republic of Macedonia

Abstract: Noninvasive urine screening for Chlamydia trachomatis infections offers a valuable public health tool, that could be of vast importance in Chlamydia control programs. The goal was to determine the prevalence of C. trachomatis infections among a sexually active population, to define the epidemiological factors associated with it, and to develop potential selective screening strategies among asymptomatic individuals in the Republic of Macedonia, using a highly sensitive and specific DNA amplification method for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 12 publications
0
6
1
Order By: Relevance
“…This was, in comparison to other similar studies conducted in Serbia, lower by about 3-5 times (8,9). On the other hand, compared to other studies carried out in the FYR of Macedonia, our results are either higher for more than two times or lower for about a quarter to a third (13,14). The data from Montenegro also show considerable variability and results for the general population are closer to those in Pomoravlje County than to the data from Skopje (12).…”
Section: Discussioncontrasting
confidence: 44%
See 1 more Smart Citation
“…This was, in comparison to other similar studies conducted in Serbia, lower by about 3-5 times (8,9). On the other hand, compared to other studies carried out in the FYR of Macedonia, our results are either higher for more than two times or lower for about a quarter to a third (13,14). The data from Montenegro also show considerable variability and results for the general population are closer to those in Pomoravlje County than to the data from Skopje (12).…”
Section: Discussioncontrasting
confidence: 44%
“…The survey conducted in Montenegro found the prevalence of chlamydial infection of 4.17% in the general population but for the subgroup of women aged 26-35 years the frequency was ten times greater (47.8%) (12). In the Former Yugoslav Republic (FYR) of Macedonia, the screening on Chlamydia trachomatis in group of women and men selected from the general population found this infection in 1.6% (95% confidence interval 0.8-2.4%) among persons without genitourinary infection symptoms and in 6.2% (3.1-9.3%) of symptomatic subgroup (13). The additional, small-size study in this country reported 24.3% prevalence of Chlamydia trachomatis presence in genitourinary system in woman (14).…”
Section: Introductionmentioning
confidence: 99%
“…Studies rated as 'marginal' (24%) 7,[30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46] , 'acceptable' (41%) , and 'commendable' (28%) 4,78-97 were retained in the review. Table 4 summarizes the 70 studies that were retained for further assessment.…”
Section: Assessment Of Included Studiesmentioning
confidence: 99%
“…The prevalence pattern worldwide among the general population ranges between 1.5% and 9% (Jascheck et al, 1993;Mulhall et al,1995;Stary et al, 1996;Morre et al, 1999;De Barbeyrac et al, 2000;Spasovski et al, 2005).…”
Section: Discussionmentioning
confidence: 96%